Assessment of fish protein hydrolysate as a substitute for fish meal in white shrimp diets: impact on growth, immune response, and resistance against Vibrio parahaemolyticus infection - Tran, Hoang Trieu Quan; Ho, Thi Hang; Nan, Fan-Hua; Liu, Chun-Hung; Hu, Yeh-Fang; Chong, Chou Min; de Cruz, Clement R.; Karim, Murni; Liu, Ting-Jui; Kuo, I-Pei; Lee, Po-Tsang (Academic Press, 2024)
This study investigated the effects of fish protein hydrolysate derived from barramundi on growth performance, muscle composition, immune response, disease resistance, histology and gene expression in white shrimp (Penaeus vannamei). In vitro studies demonstrated FPH enhanced mRNA expressions of key immune-related genes and stimulated reactive oxygen species (ROS) production and phagocytic activity in shrimp hemocytes. To evaluate the effects of substituting fish meal with FPH in vivo, four isoproteic (43 %), isolipidic (6 %), and isoenergetic diets (489 kcal/100 g) were formulated with fish meal substitution levels of 0 % (control), 30 % (FPH30), 65 % (FPH65), and 100 % (FPH100). After 8-week feeding, the growth performance of FPH65 and FPH100 were significantly lower than that of control and FPH30 (p < 0.05). Similarly, the midgut histological examination revealed the wall thickness and villi height of FPH100 were significantly lower than those of control (p < 0.05). The shrimps were received the challenge of AHPND + Vibrio parahaemolyticus at week 4 and 8. All FPH-fed groups significantly enhanced resistance against Vibrio parahaemolyticus at week 4 (p < 0.05). However, this protective effect diminished after long-period feeding. No significant difference of survival rate was observed among all groups at week 8 (p > 0.05). The expressions of immune-related genes were analyzed at week 4 before and after challenge. In control group, V. parahaemolyticus significantly elevated SOD in hepatopancreas and Muc 19, trypsin, Midline-fas, and GPx in foregut (p < 0.05). Moreover, hepatopancreatic SOD of FPH65 and FPH100 were significantly higher than that of control before challenge (p < 0.05). Immune parameters were measured at week 8. Compared with control, the phagocytic index of FPH 30 was significantly higher (p < 0.05). However, dietary FPH did not alter ROS production, phenoloxidase activity, phagocytic rate, and total hemocyte count (p > 0.05). These findings suggest that FPH30 holds promise as a feed without adverse impacts on growth performance while enhancing the immunological response of white shrimp.